KEMANUNGGALAN DALAM YOHANES 15:7 SEBAGAI MISI KONTEKSTUAL KEPADA PENGANUT KEJAWEN - Dicky Dominggus (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
This article discusses the oneness in John 15:7 as a contextual mission attempt to the Kejawen practitioners. John 15:7 is explained that if humans are in God and God is in humans, then all that people want will be fulfilled. In the Kejawen teaching, there is also an understanding of oneness, called Manunggaling Kawula Gusti. The concept is also the unification between man and God. The merger of Man with God in this concept through the stages of changing human life. From that definition, the legacy in John 15:7 has similarities with those in the Manunggaling Kawula Gusti concept. For this reason, both can be compared by looking at their similarities and differences. The result obtained from this comparison can be used as a contextualization mission to the Kejawen believers. The method used in this study is qualitative research with the literature study approach and comparisons.